Pulmonary inflammation impacts on CYP1A1-mediated respiratory tract DNA damage induced by the carcinogenic air pollutant benzo[a]pyrene - Arlt, Volker M.; Frei, Eva (Toxicological sciences, 2015)
Abstract. Pulmonary inflammation can contribute to the development of lung cancer in humans. We investigated whether pulmonary inflammation alters the genotoxi